2022
DOI: 10.3390/cells11020214
|View full text |Cite
|
Sign up to set email alerts
|

One-Carbon Metabolism: Pulling the Strings behind Aging and Neurodegeneration

Abstract: One-carbon metabolism (OCM) is a network of biochemical reactions delivering one-carbon units to various biosynthetic pathways. The folate cycle and methionine cycle are the two key modules of this network that regulate purine and thymidine synthesis, amino acid homeostasis, and epigenetic mechanisms. Intersection with the transsulfuration pathway supports glutathione production and regulation of the cellular redox state. Dietary intake of micronutrients, such as folates and amino acids, directly contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 258 publications
(281 reference statements)
0
24
0
1
Order By: Relevance
“…This study adds to effort to decipher how specific cell cycle processes are linked to the enzymes of 1C metabolism. The results we presented could also inform research that may not be focused on cell cycle progression, especially in the context of several recent studies linking 1C metabolism with longevity mechanisms in multiple systems (Maitra et al 2020;Enriquez-Hesles et al 2021;Annibal et al 2021;Lionaki et al 2022)…”
Section: Discussionmentioning
confidence: 60%
“…This study adds to effort to decipher how specific cell cycle processes are linked to the enzymes of 1C metabolism. The results we presented could also inform research that may not be focused on cell cycle progression, especially in the context of several recent studies linking 1C metabolism with longevity mechanisms in multiple systems (Maitra et al 2020;Enriquez-Hesles et al 2021;Annibal et al 2021;Lionaki et al 2022)…”
Section: Discussionmentioning
confidence: 60%
“…One plausible explanation could be the potential role of B vitamins in DNA methylation processes. These nutrients play a key role in one-carbon metabolism and their deficiency could significantly reduce DNA methylation, leading to epigenome-dependent changes in the expression of disease-related factors [ 18 , 45 , 46 ]. Dysregulation in one-carbon metabolism are linked to many neurodegenerative and age-related diseases [ 46 ] and folate deficiency could have deleterious effects on cells by allowing homocysteine accumulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These nutrients play a key role in one-carbon metabolism and their deficiency could significantly reduce DNA methylation, leading to epigenome-dependent changes in the expression of disease-related factors [ 18 , 45 , 46 ]. Dysregulation in one-carbon metabolism are linked to many neurodegenerative and age-related diseases [ 46 ] and folate deficiency could have deleterious effects on cells by allowing homocysteine accumulation [ 45 ]. Hyperhomocysteinemia is a risk factor for many age-related diseases, and observational studies have shown that individuals with advanced AMD have higher serum homocysteine concentrations [ 13 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“… Martín-Masot et al (2020) were the first to describe metabolic deficiencies in OCM in patients with CD. OCM is a network of biochemical reactions in which one-carbon units are transferred to various biosynthetic pathways; folic acid and methionine cycles are two important components of this network ( Newman and Maddocks, 2017 ; Pan et al, 2021 ; Lionaki et al, 2022 ). They are functionally used for biosynthesis of phospholipids, amino acids and DNA, as well as methylation of proteins, RNA, and DNA.…”
Section: Discussionmentioning
confidence: 99%